Introduction to linear circuit analysis and modelling : from DC to RF - Moura, Luis Miguel da Silva Carvalho de (Newnes, 2005)
Luis Moura and Izzat Darwazeh introduce linear circuit modelling and analysis applied to both electrical and electronic circuits, starting with DC and progressing up to RF, considering noise analysis along the way. Avoiding the tendency of current textbooks to focus either on the basic electrical circuit analysis theory (DC and low frequency AC frequency range), on RF circuit analysis theory, or on noise analysis, the authors combine these subjects into the one volume to provide a comprehensive set of the main techniques for the analysis of electric circuits in these areas. Taking the subject from a modelling angle, this text brings together the most common and traditional circuit analysis techniques (e.g. phasor analysis) with system and signal theory (e.g. the concept of system and transfer function), so students can apply the theory for analysis, as well as modelling of noise, in a broad range of electronic circuits. A highly student-focused text, each chapter contains exercises, worked examples and end of chapter problems, with an additional glossary and bibliography for reference. A balance between concepts and applications is maintained throughout. The book is also supported by a companion website, featuring a full solutions manual, additional equations, graphs and illustrations for Lecturers to download when preparing teaching aids, as well as numerous case studies, worked examples and exercises using MATLAB to aid student learning. Luis Moura is a Lecturer in Electronics at the University of Algarve. Izzat Darwazeh is Senior Lecturer in Telecommunications at University College, London, previously at UMIST. An innovative approach fully integrates the topics of electrical and RF circuits, and noise analysis, with circuit modelling Highly student-focused, the text includes exercises and worked examples throughout, along with end of chapter problems to put theory into practice The companion website for the book features additional exercises and a full solutions manual to aid student learning.